The Insights of Glocalization In Islamic Primary Education - Suci, Dewi Nur; Puspitasari, Intan Nuyulis Naeni (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
The expansion of internationalization has challenged education advancement in 21th century which is not only at Islamic higher education level but also at the Islamic primary education sphere. For preparing young learners to engage in the dynamics of internationalization, some Islamic primary schools competitively share new horizons on integrating sciences, humanism and spiritual values that adapt salaf models of pesantren and global ideas. Therefore, this article, in a qualitative research, exemplifies the social phenomena on how to construct new paradigm of glocalization for the evolvement andperpetuation of Islamic primary educational institution in Indonesia. Collected by observations, interviews and documentations, it is concluded that glocalization can be employed as the panacea for society’s needs in which local wisdom can take its portions in curriculum that inserts multiple intelligence and Higher Order Thinking Skill (HOTS) and provide academic agendas of primary instructional classroom.